Exploring complex and big data - Stefanowski, Jerzy; Krawiec, Krzysztof; Wrembel, Robert (Zielona Góra: Uniwersytet Zielonogórski)
This paper shows how big data analysis opens a range of research and technological problems and calls for new approaches. We start with defining the essential properties of big data and discussing the main types of data involved. We then survey the dedicated solutions for storing and processing big data, including a data lake, virtual integration, and a polystore architecture.
Keywords: big data; complex data; data integration; data provenance; data streams; deep learning